2007
DOI: 10.2176/nmc.47.89
|View full text |Cite
|
Sign up to set email alerts
|

Local Administration of Amphotericin B Against Aspergilloma in the Prepontine Cistern-Case Report-

Abstract: A 21-year-old man presented with aspergilloma in the prepontine cistern that developed after treatment for cerebellar hematoma following rupture of an arteriovenous malformation. He became bedridden with neurological signs of tetraparesis, disturbed ocular movement, and bulbar palsy, despite alert consciousness. Repeat magnetic resonance imaging 1 year later revealed a space-occupying lesion in the prepontine cistern along the clivus. This multilobular enhanced mass lesion gradually enlarged towards the brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Nabika et al [ 36 ] reported that surgical reduction of aspergilloma combined with local administration of antifungal was a good treatment option, corroborating the present study. According to Pianetti et al [ 25 ], fungal infections observed as a mass should be treated by aggressive surgical resection.…”
Section: Discussionsupporting
confidence: 90%
“…Nabika et al [ 36 ] reported that surgical reduction of aspergilloma combined with local administration of antifungal was a good treatment option, corroborating the present study. According to Pianetti et al [ 25 ], fungal infections observed as a mass should be treated by aggressive surgical resection.…”
Section: Discussionsupporting
confidence: 90%
“…Surgery not only afforded the opportunity to address the patient's symptoms in the immediate term, but also provided biopsy material that guided further management to ensure a long-term, uneventful recovery. Our strategy was consistent with that of Nabika and colleagues (6), who adopted an invasive approach to treating a patient with HIV infection and an aspergilloma in the prepontine cistern, and underlines the importance of diagnosing and treating cerebral aspergillosis promptly. As cases are rare, there is little evidence to guide clinical decision-making when treating these life-threatening superinfections, with a particular deficit of outcome data.…”
Section: Discussionsupporting
confidence: 76%
“…This prompted us to start intralesional liposomal amphotericin B administration via an Ommaya reservoir, in conjunction with continued systemic therapy with isavuconazole. A small number of cases have reported intralesional amphotericin B administration for cerebral aspergillosis, administering liposomal amphotericin B at a dose of 1 to 3 mg once weekly [ 5 , 16 , 17 ]. We chose to administer the antifungal twice weekly and at a dose of 5 mg (a scheme that has been proposed by Schauwvlieghe et al but had never been tested in practice) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%